Advantages and prospects of robotic surgery for colorectal cancer - Qi Fan; Zhengwei Fu; Dehai Xiong (Intelligent Surgery)
This paper provides an overview of the development, technical features and current applications of the da Vinci surgical robots in colorectal cancer surgeries and conducts an in-depth analysis of the precision and stability of the da Vinci surgical robots in surgeries, as well as its technical advantages in reducing surgical trauma and accelerating recovery. This paper evaluates the clinical efficacy and safety of da Vinci surgical robotic-assisted surgery through a comparison of partial clinical data with traditional surgical methods, particularly focusing on the economic and social benefits. It fully demonstrates the advantages and application prospects of the da Vinci surgical robots in colorectal surgery, including intelligent precision technology, good clinical outcomes and excellent cost-effectiveness, while also discussing the current challenges and countermeasures.